EFFECT OF INTERVENTION ON THE CONTROL OF RISK FACTORS IN CORONARY ARTERY DISEASE PATIENTS - Rauf, Muhammad Abdur; Aman, Wahaj; Shah, Syed Tahir; Khan, Noman; Khan, Sher Bahadar; Khan, Imtiaz; Mahmood, Nida; Hafizullah, Mohammad (Journal of Postgraduate Medical Institute, 2012)
Objective: To assess the effect of optimal medical therapy on the control of risk factors in coronary artery disease (CAD) patients with or with-out intervention. Methodology: It was a cross sectional comparative study carried out at Lady Reading Hospital, Peshawar January to December 2010. Subjects were divided into two groups based on percutaneous coronary intervention and optimal medical therapy. Study variables were smoking, physical activity, dyslipidemia, diabetes, hypertension and obesity. Informed written consent was taken from all the study participants. Data was recorded on a preformed Questionnaire and analyzed with SPSS version 16. P-value of 0.05 was taken as significant. Results: A total of 315 patients were studied. Baseline characteristic were similar between groups. Smoking was decreased significantly in(PCI group) as compared to (OMT group) (p=0.027). Physical activity goal â‰¥ 150 min/ week were achieved more in (PCI group) compared to (OMT group)(p=0.019). Goals set for Serum cholesterol, HbA1c%, serum LDL, Systolic blood pressure and Diastolic blood pressure have significantly achieved in (PCI group) as compared to (OMT group) with p- valves of (0.018,0.027,0.023,0.033 and 0.017) respectively. While goals set for Triglycerides, serum HDL and BMI have no significant difference between the two groups with p-valves of (0.223, 0.089 and 0.164 respectively). Conclusion: Patients who underwent intervention and remained on optimal medical therapy were more adherent to regular exercise and good compliance which lead to better risk factors control for coronary artery disease as compared to patients who remained on optimal medical therapy alone.